Uniform hazard versus uniform risk bases for performance based earthquake engineering of light-frame wood construction. - Li, Yue
This paper investigates the implications of designing for uniform hazard versus uniform risk for light-frame wood residential construction subjected to earthquakes in the United States. Using simple structural models of one-story residences with typical lateral force resisting systems (shear walls) found in buildings in western, eastern and central regions of the United States as illustrations, the seismic demands are determined using nonlinear dynamic time history analyses, whereas the collapse capacities are determined using incremental dynamic analyses. The probabilities of collapse, conditioned on the occurence of the maximum considered earthquakes and design earthquakes stipulated in ASCE Standard 7-05 and the collapse margins of these typical residential structures are compared for typical construction practices in different regions in the United States. THe calculated collapse inter-story drifts are compared with the limits stipulated in FEMA 356/ASCE Standard 41-06 and observed in the recent experimental testing. The results of this study provide insights into residential building risk assessment and the relation between building seismic performance implied by the current earthquake resistant design and construction practices and performance levels in performance based engineering of light frame wood construction being considered by the SEI/ASCE committee on reliability based design of wood structures. Further code developments are necessary to achieve the goal of uniform risk in earthquake resistant residential construction.
Keywords: Buildings; Collapse; Earthquakes; Fragility; Limit states; Performance-based engineering; Reliability; Structural engineering; Wood structures